Beyond capitalism and liberal democracy: On the relevance of GDH Cole's sociological critique and alternative. (January 2016) - Masquelier, Charles; Dawson, Matt
This article argues for a return to the social thought of the often ignored early 20th-century English thinker GDH Cole. The authors contend that Cole combined a sociological critique of capitalism and liberal democracy with a well-developed alternative in his work on guild socialism bearing particular relevance to advanced capitalist societies. Both of these, with their focus on the limitations on 'free communal service' in associations and the inability of capitalism to yield emancipation in either production or consumption, are relevant to social theorists looking to understand, critique and contribute to the subversion of neoliberalism. Therefore, the authors suggest that Cole's associational sociology, and the invitation it provides to think of formations beyond capitalism and liberal democracy, is a timely and valuable resource which should be returned to.